Land Use Transformation and Changes in Built Heritage Character of Residential Neighborhood Corridors within the Cultural Heritage Conservation Context Comparative Study between Senopati Street – Kebayoran Baru, Jakarta and Progo Street, Bandung - Kartidjo, Woerjantari Soedarsono; Victoryka, Nadya; Yogaswara, Raden Agung; Imanullah, Hadi Ilhami (Universitas Indonesia, 2019)
Urban built cultural heritage are currently facing a great threat from development pressure particularly in developing countries as a result of population growth, urban development, as well as economic growth, no exception to Indonesia. Jakarta and Bandung as one of the most established and fast growing metropolitan in Indonesia in terms of population and economy are struggling to conserve their urban built cultural heritage. Although national law have encourage cultural heritage conservation management in maintaining the existence of these historic residential neighborhood areas, both cities are still gradually suffering losses of distinctive character and appearance. Whether through process of adaptive reuse, renovations, and even replacement, these changes detract from the townscape value of these invaluable urban assets. This problem is found quite evident throughout Jakarta and Bandung. This paper summarizes the findings of research carried out into the gap between spatial planning regulations and practice of two different Indonesian cities in relation to the urban heritage conservation of two historical residential corridors in Senopati Street - Kebayoran Baru, Jakarta and Progo Street, Bandung. It reviews and compares the effectiveness of different spatial planning regulations approaches of respective cities on delivering the urban heritage conservation outcomes in attempt to find a solution and establish as well as indicate ways of improving the cultural heritage regulations in Indonesia. The research explores the land use transformation and changes of urban built heritage character and appearance of historical residential neighborhood areas along both observed corridors and questions the extent of these transformation and changes occurred in both locations. The research presents a method for measuring changes of land use and physical character in the historic built environment and descriptive analyses factors that might affect the loss of built heritage character in both areas